New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil - Gonçalves, Maísa De Carvalho; Novaes, Marcos Carneiro; Salles, Frederico Falcão (Zootaxa, 2017)
Two new species of the perlid genus Anacroneuria, A. rotunda n. sp and A. pitii n. sp are described from Espírito Santo State, Brazil. Additionally, six species of Anacroneuria and four species of Kempnyia are reported for the first time from Espírito Santo State. Records are also provided for A. debilis, A. subcostalis, K. flava, K. gracilenta, and K. neotropica. An undetermined species of Macrogynoplax based on nymphs is also reported from Espírito Santo State